The Asymmetric Impact of Exchange Rate on the Inflation Rate in Sierra Leone (Global Business Management Review (GBMR), 2019)
The paper is aimed at investigating empirically, the impact of exchange rate on inflation and the extent of its asymmetry. The econometrics tool of analysis utilized by this study is Autoregressive Distributed Lag Model (ARDL) and Non-linear ARDL (NARDL) using time series data of Sierra Leone for a period 1970 - 2016. The results of the ARDL indicated that the exchange rate is inflationary but only in the short-run. There is no evidence of the long- run influence of exchange rate on inflation in the country. Meanwhile, the results of the NARDL not only confirms the short-run inflationary of the positive shocks of the exchange rate, but it also signifies the disinflationary effect of the negative shocks during the long-run. The findings of the research are limited to Sierra Leone whose data were used, based on ARDL and NARDL as the econometrics techniques applied, on the country’s data from 1970 to 2016 as well as the variables that are chosen. This implies that devaluation of local currencies in Sierra Leone can immediately raise the level of prices of imported commodities, in particular, and immediately raise the level of inflation in the country in general, but such effects are limited to the short-run, while revaluation has a disinflationary effect in the long- run.